2013
DOI: 10.1159/000353105
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus Genotype D Predominates HBsAg-Positive Egyptian Blood Donors and Is Mainly Associated with a Negative HBeAg Serostatus

Abstract: Objectives: Hepatitis B virus (HBV) infection is a global health burden. In this regard, Egypt has an intermediate HBV seroprevalence. HBV is classified into ten different genotypes (A-J) with different geographic distributions. Genotype D is the most prevalent in the Middle East. Limited data are available about HBV genotyping among Egyptian blood donors, particularly in Upper Egypt. We examined the seroprevalence of HBV among 12,000 blood donors attending the blood transfusion services center in Minia Govern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 38 publications
4
3
1
Order By: Relevance
“…HBV-genotype D2 was the most prevalent genotype in our patients (98.2%) and this is consistent with previous data obtained in Egypt [Habil et al, 2013;Zaky et al, 2010]. As regards, the serological and virological markers of HBV in the whole studied group, HBeAg-negative and HBeAb positive patients were 81.9% and 76.7%, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…HBV-genotype D2 was the most prevalent genotype in our patients (98.2%) and this is consistent with previous data obtained in Egypt [Habil et al, 2013;Zaky et al, 2010]. As regards, the serological and virological markers of HBV in the whole studied group, HBeAg-negative and HBeAb positive patients were 81.9% and 76.7%, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…In the present work, fifteen (14.5%) donors were positive for HBeAg and comparable with other studies in Tanzania [ 21 ], Egypt [ 49 ], and Poland[ 47 ] but lower than reports from Ethiopia[ 50 ]and Benin [ 51 ]. Seropositivity for HBeAg, a marker of active viral replication and high infectiousness, is associated with higher risk for hepatocellular carcinoma; and it is significant regardless of serum level of ALT and status of liver cirrhosis[ 52 ].…”
Section: Discussionsupporting
confidence: 91%
“…In our study, ninety-eight (95.1%) of donors had ALT level below 1.5xULN, it is comparable to data reported in asymptomatic HBV carrier blood donors [ 15 , 47 , 49 ]. Those donors who had elevation of ALT level above 1.5xULN showed also higher viral load value, even if the relation was statistically insignificant ( p = 0.060).…”
Section: Discussionsupporting
confidence: 88%
“…were HBeAb-positive. Nonetheless, HBeAg seropositivity for HBV-infected blood donors in our study was lower than those reported from Ethiopia [28], Egypt [29] and Tanzania [30]. HBeAg, a marker of active viral replication and higher infectiousness, is associated with higher risk for liver cirrhosis and hepatocellular carcinoma [31].…”
Section: Discussioncontrasting
confidence: 66%